Advanced assessment of the physicochemical characteristics of Remicade® and Inflectra® by sensitive LC/MS techniques. Issue 6 (17th August 2016) - Fang, Jing; Doneanu, Catalin; Alley, William R.; Yu, Ying Qing; Beck, Alain; Chen, Weibin
ABSTRACT: In this study, we demonstrate the utility of ultra-performance liquid chromatography coupled to mass spectrometry (MS) and ion-mobility spectrometry (IMS) to characterize and compare reference and biosimilar monoclonal antibodies (mAbs) at an advanced level. Specifically, we focus on infliximab and compared the glycan profiles, higher order structures, and their host cell proteins (HCPs) of the reference and biosimilar products, which have the brand names Remicade® and Inflectra®, respectively. Overall, the biosimilar attributes mirrored those of the reference product to a very high degree. The glycan profiling analysis demonstrated a high degree of similarity, especially among the higher abundance glycans. Some differences were observed for the lower abundance glycans. Glycans terminated with N-glycolylneuraminic acid were generally observed to be at higher normalized abundance levels on the biosimilar mAb, while those possessing α-linked galactose pairs were more often expressed at higher levels on the reference molecule. Hydrogen deuterium exchange (HDX) analyses further confirmed the higher-order similarity of the 2 molecules. These results demonstrated only very slight differences between the 2 products, which, interestingly, seemed to be in the area where the N-linked glycans reside. The HCP analysis by a 2D-UPLC IMS-MS approach revealed that the same 2 HCPs were present in both mAb samples. Our ability to perform these types of analyses and acquire insightful data for biosimilarity assessment is based upon our highly sensitive UPLC MS and IMS methods.